Administration of Electronic Election Process Dispute in the State Administrative Court - Ningrum, Intan Sari Widya (Law Research Review Quarterly, 2018)
Elections constitute one of the manifestations of democratic people's sovereignty in accordance with the ideals of the state. Election process disputes are litigation efforts that are filed as a result of the issuance of KPU Decree submitted to PTUN. Examining the electoral dispute settlement arrangements electronically and explaining how resolution is the aim of this study. The method used is normative juridical research. The results showed that the electoral dispute resolution process was regulated electronically in Law Number 7 of 2017 concerning Elections, Supreme Court Regulation (Perma) Number 3 of 2018 concerning Case Administration in Electronic Courts, Perma Number 5 of 2017 concerning Procedures for Dispute Resolution Election Process in PTUN, Decision of Chief Justice of the Supreme Court Number 122 / KMA / SK / VII / 2018 concerning Guidelines for Registered User Governance of Court Information System, and Decree of the Director General of Military Courts and State Administrative Courts of the Supreme Court of the Republic of Indonesia Number: 307 / Djmt / Kep / 5/2018 concerning Implementation Guidelines for Perma Number 3 Year 2018. The trial stage of the dispute of the general election process begins with the reading of the lawsuit, the answers, the proof, and the verdict. Acceptance of lawsuits, answers, management, submission, and storage of State administrative case documents can use an electronic system through the e-Court application at the site address http://ecourt.mahkamahagung.go.id. With the existence of Perma Number 3 of 2018 will accelerate the process of electoral dispute resolution.